THE INFLUENCE OF WORK ENVIRONMENT, WORK DISCIPLINE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Delva Nizar Mirandani; Syaiful Bahri (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to examine the relationship between the work environment, work discipline and job satisfaction with employee performance at the Representative Office of the Population Agency and theNational Planning Agency (BKKBN) of North Sumatra. This study used a quantitative type of research and used an associative approach, the sample from this study was taken from all permanent employees at the Representative Office of the National Population and Family Planning Agency (BKKBN) north Sumatra which amounted to 84 employees. Data collection techniques used with media interviews, documentation studies and questionnaires (questionnaires). Data analysis techniques in this study used classical assumption tests, multiple linear regression and hypothesis tests. The results of this study show that the work environment has a positive but not significant effect on employee performance. Work discipline has a positive but insignificant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance.